2004
DOI: 10.1016/j.cell.2004.08.025
|View full text |Cite
|
Sign up to set email alerts
|

JunD Reduces Tumor Angiogenesis by Protecting Cells from Oxidative Stress

Abstract: Reactive oxygen species (ROS) are implicated in the pathophysiology of various diseases, including cancer. In this study, we show that JunD, a member of the AP-1 family of transcription factors, reduces tumor angiogenesis by limiting Ras-mediated production of ROS. Using junD-deficient cells, we demonstrate that JunD regulates genes involved in antioxidant defense, H2O2 production, and angiogenesis. The accumulation of H2O2 in junD-/- cells decreases the availability of FeII and reduces the activity of HIF pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
418
4
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(442 citation statements)
references
References 55 publications
16
418
4
4
Order By: Relevance
“…Reactive oxygen species were reported to inhibit PHD activity under normoxic conditions by oxidizing the PHD cofactors ferrous iron and ascorbate (Figure 3) (Gerald et al, 2004). It is therefore tempting to speculate that ROS also play a role in the pseudohypoxic response of SDH (and maybe FH)-deficient tumours.…”
Section: Signalling By Reactive Oxygen Speciesmentioning
confidence: 99%
“…Reactive oxygen species were reported to inhibit PHD activity under normoxic conditions by oxidizing the PHD cofactors ferrous iron and ascorbate (Figure 3) (Gerald et al, 2004). It is therefore tempting to speculate that ROS also play a role in the pseudohypoxic response of SDH (and maybe FH)-deficient tumours.…”
Section: Signalling By Reactive Oxygen Speciesmentioning
confidence: 99%
“…H 2 O 2 may cause a local Fenton reaction to shift iron ions from Fe þ 2 to Fe þ 3 causing inactivation of the enzyme. 62 A combination of oxygen, iron, TCA cycle intermediate availability and ROS signaling might optimize the hydroxylation of HIFa proteins. 63 Furthermore, recent studies have indicated that HIF-1 activation might prevent excessive ROS production in hypoxic cells by regulating mitochondrial respiration through increased gene expression of PDK1 (PDH (pyruvate dehydrogenase) kinase 1) and switching of cytochrome c oxidase subunit IV isoforms.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…These most likely involve the PHDs, since recent work employing a cellular prolyl hydroxylase reporter, which utilizes hydroxylation-specific mobility shifts on SDS-PAGE gels to monitor the hydroxylation of HIFα in vivo, showed that mitochondrial inhibitors and the anti-oxidant Mito-Q affect cellular hydroxylase activity [26]. One report has shown that elevated ROS levels due to genetic ablation of the transcription factor JunD and consequent downregulation of its anti-oxidant target genes, leads to PHD2 inactivation via oxidation of ferrous iron in the catalytic domain as determined by electron paramagnetic resonance spectroscopy [80]. However, it remains to be determined whether physiological levels of ROS produced during hypoxia can have the same effect on PHD2.…”
Section: Potential Mechanisms For Ros In Cellular O 2 Sensingmentioning
confidence: 99%